2004
DOI: 10.1108/03090590410527636
|View full text |Cite
|
Sign up to set email alerts
|

Training practices and organisational learning capability

Abstract: This paper provides an in-depth study of the relationship between the company's training strategy and its learning capability. On a sample of 111 Spanish companies from the chemical industry, tests a set of hypotheses which link four different training strategies with the learning capability dimensions. The results obtained from the regression analyses clearly show that ongoing training, team-based training and job rotation programmes have a positive influence on company learning capability. The present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 104 publications
1
40
0
4
Order By: Relevance
“…Higher standards of knowledge and individual expertise among employees who work in learning intensive environments have been reported in theoretical and empirical research (Jerez‐Gómez et al, ; Liedtka, Haskins, Rosenblum, & Weber, ; McGill, Slocum, & Lei, ; Senge, ). We are especially interested in the kind of individual expertise that, in turbulent environments, is related to higher levels of (knowledge) workers’ ability and motivation to broaden the array of daily tasks/functions that they effectively carry out.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 87%
“…Higher standards of knowledge and individual expertise among employees who work in learning intensive environments have been reported in theoretical and empirical research (Jerez‐Gómez et al, ; Liedtka, Haskins, Rosenblum, & Weber, ; McGill, Slocum, & Lei, ; Senge, ). We are especially interested in the kind of individual expertise that, in turbulent environments, is related to higher levels of (knowledge) workers’ ability and motivation to broaden the array of daily tasks/functions that they effectively carry out.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 87%
“…This first dimension of employability is clearly affected by organizational learning practices: theoretical and empirical research has reported higher standards of knowledge and individual expertise among employees who work in organizational learning environments (Jerez-Gomez et al, 2004;Liedtka et al, 1997;McGill et al, 1992;Senge, 1990). The main reason for this positive connection is training.…”
Section: Occupational Expertisementioning
confidence: 93%
“…Training is considered to be one of the most significant human resource practices for the development of organizational learning capabilities (DiBella et al, 1996;McGill and Slocum, 1993;Nonaka and Takeuchi, 1995;Ulrich et al, 1993). Training practices favor the acquisition and constant generation of new knowledge and skills, consequently improving the level of occupational expertise (DiBella et al, 1996;Garvin, 1993;Jerez-Gomez et al, 2004;Lei et al, 1999;Leonard-Barton, 1992).…”
Section: Occupational Expertisementioning
confidence: 98%
“…Scholars have repeatedly claimed that training practices improve innovation by endorsing learning climate (Gómez et al, 2004; Shipton et al, 2005; Cortini et al, 2016) and exploratory learning (Shipton et al, 2006; Beugelsdijk, 2008), while, not unexpectedly, research shows that the way partners cope with the collective learning processes, communicate and cooperate plays an essential role in the success of strategic collaborations for new products and services (Larsson et al, 1998; Ceschi et al, 2014b, 2017e, 2018; Manuti et al, 2017; Scalco et al, 2018). Research also shows that people need to be trained on these issues since you cannot assume that people know how to do this spontaneously (Sartori and Scalco, 2014).…”
Section: Training and Development For Organizational Innovationmentioning
confidence: 99%